2020
DOI: 10.1039/c9sm02237f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically programmed 2D and 3D liquid crystal elastomers at macro- and microscale via two-step photocrosslinking

Abstract: A facile method for fabricating 3D-shaped liquid crystal elastomers at the macro- and microscales was developed by mechanical programming coupled with two-step photocrosslinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Compared to nematic networks, smectic networks show larger magnitudes of actuation. Traugutt et al [ 16 ] compared the influence of liquid-crystal orientation on the thermo-mechanical properties of the main chain LCEs, they found that the actuation performance, work capacity, dissipation, and elastic modulus of the LCEs are all dependent on the alignment state of the mesogenic unit during synthesis.…”
Section: Application Of Lces For Soft Robotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to nematic networks, smectic networks show larger magnitudes of actuation. Traugutt et al [ 16 ] compared the influence of liquid-crystal orientation on the thermo-mechanical properties of the main chain LCEs, they found that the actuation performance, work capacity, dissipation, and elastic modulus of the LCEs are all dependent on the alignment state of the mesogenic unit during synthesis.…”
Section: Application Of Lces For Soft Robotsmentioning
confidence: 99%
“…Therefore, the LCE networks will contract along the LC direction and expand in the vertical direction with the order–disorder transition of mesogens, resulting in the macroscopic shape changes of the bulk LCEs [ 14 , 15 ]. Similar to small molecule liquid crystals, the phase transition of LCEs can be achieved by environmental stimuli, such as temperature [ 16 , 17 ], humidity [ 18 , 19 ], organic solvent [ 20 , 21 ], electric [ 22 , 23 , 24 , 25 , 26 , 27 ], and ion [ 28 ] or remote stimuli, such as light [ 29 ], magnetic field [ 30 , 31 , 32 ], etc. Furthermore, the shape change of LCEs is fully reversible since their phase transition is dictated by thermodynamic equilibrium [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the example highlighted here, Lee and co‐workers fabricated thermoresponsive, 3D shape‐morphing LCEs in the macroscale as well as microscale. [ 116 ] The aza‐Michael addition‐based step growth polymerization used here was developed by the White group in 2015. [ 117,118 ] First, a commercially available LC monomer underwent chain extension with n‐butylamine, which resulted in a diacrylate‐functionalized poly(β‐amino ester)‐type LC oligomer.…”
Section: Synthetic Techniquesmentioning
confidence: 99%
“…LCEs are more deformable and have more versatile processing conditions than LCNs; therefore, they can be fabricated into various geometries, including 0D particles, [23] 1D fibers, [24] 2D films, [25] and complex 3D shapes. [26] Therefore, the development of a new class of humidity-responsive actuators based on LCEs is highly desirable to overcome the aforementioned challenges associated with LCNs.…”
Section: Introductionmentioning
confidence: 99%